1980
DOI: 10.1002/prep.19800050604
|View full text |Cite
|
Sign up to set email alerts
|

Shock Initiation of PBX‐9404 by electrically driven flyer plates

Abstract: The shock initiation threshold of PBX‐9404 has been studied over the pressure range 3.1 GPa‐28 GPa with pulse lengths ranging from 0.007 μs‐0.63 μs. The short‐duration, high pressure pulses were produced by the impact of thin plastic flyer plates accelerated by electrically exploded metal foils. We performed the experiments on explosive pellets 25.4 mm in diameter with thicknesses of 6.0 mm, 10.1 mm and 19.1 mm. No dependence of the initiation threshold on pellet thickness was observed. The data are represente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…A viscoelastic equation of state (EOS) for PMMA was employed. [34][35][36] For these two materials, the shock-velocity ͑U S ͒-particle-velocity ͑u p ͒ relationship is given by 21 A Mie-Grüneisen EOS was used for water 30,33 and Mylar.…”
Section: Hydrocode Modelmentioning
confidence: 99%
“…A viscoelastic equation of state (EOS) for PMMA was employed. [34][35][36] For these two materials, the shock-velocity ͑U S ͒-particle-velocity ͑u p ͒ relationship is given by 21 A Mie-Grüneisen EOS was used for water 30,33 and Mylar.…”
Section: Hydrocode Modelmentioning
confidence: 99%
“…Weingart (8) has shown that the initiation threshold for 1.80 gycm 3 TATB pellets as a function of¯yer diameter was the same for the 25.4 mm and 12.7 mm¯yers, but substantially increased as the¯yer diameter was reduced.…”
Section: Diameter Effectmentioning
confidence: 99%
“…± For PBX-9404, Figure 1 shows the new relationship compared to experimental data (Kapton¯yer plate impacts (8) ). Although the behaviour of this explosive seemed well ®tted by the original criterion, it can be shown that the new one gives a better ®t over a broader pressure range.…”
Section: (A) Heterogeneous Explosivesmentioning
confidence: 99%
“…P o is the unique value that is entered into our code models at this time. Table 1 lists the coefficients obtained from the data [4,[6][7][8][9][10][11][12] with ours and the James' methods, and there is not a lot of difference. The runs have the same flyer and explosive radii, which is 12.7 mm in most cases.…”
Section: Flyer Datamentioning
confidence: 99%
“…In Table 5, we pull together the three sources of pressure data: flyer thresholds [4,[6][7][8][9][10][11][12], calculated run-time values [11,21,[25][26][27][28][29][30][31][32][33][34][35][36][37] and the smallest gap test pressures available [15,18]. There are only a few Eglin shots, so we rely for a gap tests almost completely on the NSWC LSGT.…”
Section: Pressure Threshold Summarymentioning
confidence: 99%